(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
This contribution presents five unpublished sheets of lead with Iberian inscriptions in north-eastern Iberian writing. Three come from Castellet de Banyoles (Tivissa), and two from Masies de Sant Miquel (Banyeres del Penedès). The first one from Tivissa is a mint proof of the kuḿ legend, the second would contain a relatively long text, but only a small longitudinal fragment survives, and the third is complete, but contains a very short text: banduleis / eiar. The first one from Banyeres contains a short and fragmented text with reading problems, while the other contains a long text of which the central spine has been preserved, in which a good number of anthroponyms are identified, such as edeśigi, tigirselgi, goroigi and tautini.